Laparoscopic Repair of Postoperative Perineal Hernia - Stephen Ryan; Dara O. Kavanagh; Paul C. Neary (Case Reports in Medicine)
Perineal hernias are infrequent complications following abdominoperineal operations. Various approaches have been described for repair of perineal hernias including open transabdominal, transperineal or combined abdominoperineal repairs. The use of laparoscopic transabdominal repair of perineal hernias is not well-described. We present a case report demonstrating the benefits of laparoscopic repair of perineal hernia following previous laparoscopic abdominoperineal resection (APR) using a nonabsorbable mesh to repair the defect. We have demonstrated that the use of laparoscopy with repair of the pelvic floor defect using a non absorbable synthetic mesh offers an excellent alternative with many potential advantages over open transabdominal and transperineal repairs.